Strategi Peserta Program Keluarga Harapan (PKH) Mempertahankan Status Pesertanya; Studi Nagari Punggasan Timur Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan - Casiavera (Jurnal Masyarakat Maritim, 2019)
This study explains about PKH recipients’ strategy to accept the assistance and not to be graduated. This study used the qualitative approach using descriptive type. Informants are chosen based on purposive sampling technique while data collection applies observation technique and in-depth interview (loosely structured interview). It uses Structuration theory proposed by Anthony Giddens which focuses on duality relation between agent and structure.